High efficiency continuous-wave Ho: LSO laser wing-pumped by the laser diode at 1.91 μm - Cui, Zheng; Yu, Yong; Pan, Chao (Frontiers in Physics, 2024)
We present a high-efficiency continuous-wave Ho: LSO laser wing-pumped by a 1.91 μm laser diode. The impact of different output transmittances on the laser output power is compared and analyzed. The optimal result was achieved with a -500-mm radius curvature and a 6% transmission output coupler. The maximum output power of the Ho: LSO laser is 7.81W, with a slope efficiency of 44.7%, a center wavelength of 2106.6nm, and beam quality factors of 1.4 in the x-direction and 1.3 in the y-direction.